2023
DOI: 10.2174/18741495-v17-e230725-2023-28
|View full text |Cite
|
Sign up to set email alerts
|

Shallow and Wide RC Beams, Definition, Capacity and Structural Behavior – Gap Study

Ahmed A. Soliman,
Dina M. Mansour,
Ahmed Ebid
et al.

Abstract: Wide beam, shallow beam, and banded beam are almost equivalent terms for beams with limited depth and large width. They are often embedded in ribbed slabs to facilitate the formwork. The contribution of web reinforcement in the shear capacity of this type of beam is still a gray area, and all design codes neglected this contribution. The aim of this research is to introduce a general overview of this topic and detect the unstudied gaps in this topic. Nine design codes and about forty previous researches were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The results of these studies suggest that machine learning is a promising approach for predicting the behavior of concrete elements [32]. Soliman et al [33] identified several gaps in the previous studies and investigations regarding the shear capacity of the wide, shallow reinforced concrete beams. Most previous studies had, of course, focused on the stirrup configurations at the shallow-wide beams, as the code provisions and expressions were completely negligible for the matter as mentioned before.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies suggest that machine learning is a promising approach for predicting the behavior of concrete elements [32]. Soliman et al [33] identified several gaps in the previous studies and investigations regarding the shear capacity of the wide, shallow reinforced concrete beams. Most previous studies had, of course, focused on the stirrup configurations at the shallow-wide beams, as the code provisions and expressions were completely negligible for the matter as mentioned before.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same techniques, the mode of failure of the reinforced concrete beams can also be predicted [15]. After carefully studying the previous research and investigations, several gaps in these studies were identified and considered for this experimental investigation [16]. Previous experimental studies had only considered one aspect ratio (b/d) per study, meaning that all the specimens in the same study had the same cross section and only steel configurations or types of loading were changed during testing.…”
Section: Introductionmentioning
confidence: 99%